Differential influence of cortex and stele components on root tip diameter in different types of tropical climbing plants - Xu, Haiwu; Wang, Siyuan; Tang, Liang; Wang, Yan; Li, Zhongyue; Wang, Wenna (Frontiers in Plant Science, 2022)
Climbing plants are an abundant and taxonomically diverse plant group that competes intensely with trees and thus substantially affects forest diversity and structure. The growth and physiology of climbing plants largely depend on their root tip structure and function. However, little is known regarding the mechanisms through which anatomical traits regulate root tip diameter in climbing plants. Therefore, our study sought to explore the relationships between root tip diameter and seven anatomical traits (e.g. cortex thickness and stele diameter) in three lianas and three vine species sampled from a tropical forest in Hainan. Root tip diameter was significantly positively correlated with cortex thickness (r = 0.94–0.99) and stele diameter (r = 0.72–0.94) within species, especially with cortex thickness. Cortex thickness was significantly positively correlated with mean cortical cell diameter in six species (r = 0.72–0.93), but was only correlated with the number of cortical cell layers in three species (r = 0.42–0.66). Stele diameter displayed significant positive correlations with mean conduit diameter (r = 0.58–0.88) and the number of conduits per stele (r = 0.50–0.66, except for Cyclea hypoglauca), and was negatively correlated with conduit density in all species (r = -0.65– -0.77). The correlations between cortical cells and conduit traits and root tip diameter were similar to that with cortex thickness and stele diameter, respectively. Compared with vines, liana root tips showed closer relationships between root diameter and cortex thickness and stele diameter, and between cortex thickness and mean diameter of cortical cells. Moreover, the root tip of lianas possesses significantly higher stele proportion and denser conduits, significantly lower cortex proportion, and smaller conduit size than those of vines. However, the specific conductivity was similar. Overall, these results suggest that the cortex is the main driver for the change in root tip diameter rather than the stele. Nevertheless, both factors were responsible for variations in diameter-related traits when compared with number-related traits, with lianas and vines exhibiting distinct regulatory mechanisms.